The Pain of sleep loss and Cogitative neuroscience: descriptive review - yagnik, karan (Innovative Journal of Medical and Health Sciences, 2021)
Background: Sleep Loss increase sensitivity and hence increases the experience of pain. Tension of Sleep loss is also painful. One of the reason of sleep loss on pain shows the association between sleep and pain. Material and Method: Lot of statistical data is available on various artherticwebpage. Peer reviewed research papers and survey results has taken into account. Tedfalk and webinar discussion are important for searching guidelines. Workshop and symposium published papers are also part of the discussion we have taken book chapters as a working guideline Result: The sleep loss and pain, in language of mathematics, not function but functional. Revision We have two different types of studies results are available 1. In hospital and laboratory, results of patients test and its analysis. 2. On paper or online serve results many researchers try hard to analogize successfully. Conclusion: There is strong function relation between loss of sleep and pain brain mechanism also proved in laboratory fram and patient’s serves and opinions. Medication, physiotherapy can give result but it varies from person to person